Self Medication of Anti-microbial Agents (AMAs) and Over-the-Counter Practices: A Study in Mymensingh Sadar Area (Community Based Medical Journal, 2013)
Self-medication is common in countries where prescription legislations are not strong enough and drugs are available over the counter. This study was conducted to assess the self-medication by antibiotics in Mymensingh Sadar Area population and determine the factors related to it. This descriptive study was conducted in Mymensingh Sadar Area between January 2010 and December 2010. Convenient sampling was used to select respondents from among those who came to the community pharmacies to purchase drugs for self-medication. Respondents were interviewed after they made their requests but before they were provided with information on the drugs they requested. Data were collected using structured questionnaire. Drug consumers consisted of all age categories of both genders; as well as different occupations of varying educational background levels. The most frequently reported illnesses that prompted self-medication of respondents were fever, dental pain, cough & common cold, dermatological and ENT problems. Over 42% of them made their requests by telling symptoms of illness and 32.3% obtained advice from traditional healers. The most common reasons reported for self-diagnosis and self-medication were cost of physician service and non-seriousness of the disease. More than 13 different types of antibiotics were requested, the most frequent category of antibiotics being ciprofloxacin/other FQS 21%, amoxicillin 16.5%, azithromycin/erythromycin 14% and cephalosporin 13.3%. Self-medication is widely practiced for a wide range of illnesses or symptoms of illnesses and for over-the-counter. The public as well as the health care providers have to be educated on the scopes of self-medication; i.e., the type of illnesses to be self-diagnosed and self-treated and the type of drug products to be used in order to promote responsible self-medication. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14176 Community Based Medical Journal Vol.2(1) 2013 15-20